Performance Appraisal and Employee Performance in Tertiary Institutions: A Study of National Teachers’ Colleges. - Ndagire, Immaculate (Kabale University, 2024)
This study examined the effect of performance appraisal and employee performance of National Colleges a case of National Teacher’s College Kabale, Mubende, and Kariro. Performance appraisal was an independent variable and employee performance was a dependent variable. A descriptive design was used for the investigation. A combination of quantitative and qualitative analysis was conducted on data received from 139 respondents. The data were presented using frequency tables because the descriptive analysis involved describing a single variable and its characteristics. To determine the associations between the predictor and dependent variables at the bivariate level, a Pearson correlation matrix analysis was carried out. A linear regression model was used to fit the data. Research findings from the regression model show that performance standards (R=862), performance measurement (R=756 and result dissemination (R=829) have a positive significance on the employee’s performance at National Teachers’ Colleges. The main conclusion drawn from this research is that Performance appraisal is a systematic evaluation of employee performance, which is crucial in educational settings, particularly in tertiary institutions like National Teachers’ Colleges (NTCs). It serves multiple purposes, including enhancing employee performance, providing feedback, and identifying areas for professional development. In the context of NTCs, the effectiveness of performance appraisal systems can significantly influence overall employee performance and institutional success. Therefore, the study suggests that in order for National Teachers’ Colleges to become accustomed to improving financial performance, more work needs to be done on performance standards, performance assessment, and result distribution.